Adesão de professores ao uso do Sistema de Frequência Modulada em estudantes com deficiência auditiva - Esturaro, Giovana Targino (2016)
The FM system (frequency modulation) is a wireless technology, usually coupled with hearing aids and cochlear implants, in order to help users with electronic devices to understand speech in situations where there is noise, reverberation or when the speaker is distant. In June 2013, it was published the document 1,274 / GM / MS, which allows access to assistive devices (FM) for children aged 5 to 17 years with auditory ability of speech recognition. Objective: To describe and analyze the process of adaptation and consistency of use of Frequency Modulation System - FM in the classroom, particularly the adhesion of the teacher in this process and the identification of factors favoring adaptation. Method: The study included 69 children between five and 17 years, who received the FM system at Centro Audição na Criança e Clínica Mauro Spinelli (CeAC - DERDIC) in 2015. The teachers of the students were invited to participate in the study responding to the questionnaire SIFTER, teacher classification, which was delivered with a manual of good practice for the use of FM systems. Some school visits were conducted. Results: 39 responses were received, but only for 36 (92.3%) it was possible to obtain data of consistency measured by records in FM transmitter. Of these, 13 subjects (36.1%) were consistent use of FM and 23 (63.9%) were considered inconsistent use of the system in school and there was no significant difference between the groups when compared gender, economic class, schooling mother, hearing loss, regular or special school, type of school and child education. From the teachers responses analysis it was concluded that: only 42% (n = 15) of the teachers know the student's hearing loss characteristics. There was no significant difference between the use of consistency and school performance when considering the three categories of the scale used (approved, limit and failure), as the responses of teachers in SIFTER scale. Conclusion: It is necessary actions in the health and education area in order to have success in using the FM system at school, and is essential to school participation, health services and parents to adherence to treatment